Growing into an Innovative Economy: Evidence from Chinese Firm-Level Data Analysis - Zhou, Yixiao (ANU E Press, 2013)
The Chinese economy is undergoing profound change in policy and structure. The change is necessary to increase the value of growth to the Chinese community, and to sustain growth into the future. The changes are so comprehensive and profound that they represent a new model of Chinese economic growth. This book describes the replacement of an old uninhibited investment expansion model of growth, by transition to modern economic growth and provides insights into recent changes and where they are likely to lead. These include requirements for building the new institutions including its public finances for future growth, adjustments in its savings, industry and agriculture, changes in its demographic structure, business environment, and pattern of rural-urban migration, prospects for ‘green growth’, its energy policy trilemma and the climate change mitigation strategy, and changes for China’s interaction with the international economy through its overseas investment and trade in high tech products. China’s adoption of a new model of economic growth is of immense importance to people in China and everywhere. This book is an early attempt to take a close look at many of the features of the new model.